Representações, discursos e novas institucionalidades: estudo de caso sobre a dinâmica do uso da água entre produtores de arroz do extremo sul do Brasil - Silva, Monica Anselmi Duarte da (2008)
The 1988 Constitution brought about significant changes in the Brazilian legislation, particularly those related to the property rights on rural estates. Besides that, substantial changes were introduced in relation to the usage of natural recourses, as it is the case of water, raised to the common welfare category, as a finite character and provided with economic value. For this account, important limitations were imposed to the private property, which only now begin to be embodied into the imaginary of social actors involved in productive processes which act in the sector of production systems. These changes have engendered a necessity for new institutionalities as well as of invariably adaptations considered as a resistance on the part of the gaucho agrarian bourgeoisie. This is precisely the case of rice producers, who are considered as one of the sectors imposing a new dynamics on the socio-productive relationships from the process of modernization since the second half of the XX century, achieving as expressive expansion on the cultivated areas, rice production and productivity, as well as on the hydric consumption required for this culture. This dissertation analyzes these questions based on a case study performed in the municipality of Santa Vitoria do Palmar, the extreme gaucho south. The search stands from the premise that this fraction of the gaucho bourgeoisie detains a vision of the world as to the hydric recourses which is expressed not only on the point of view of its practices and ways ok management of these recourses but also on a forged discourse coming from a historical, political and social context in which they are inserted. The discourse analysis allowed to identify clear elements which show not only the resistance of these producers in relation to new institutionalities as well as the means through which the Brazilian State intends to promote the shared management of the hydric recourses. The appropriative, patrimonial and immediative concept of the producers imposed itself upon the study about the rice producers representations of this gaucho region, strongly tributary of the rice production performance and the extensive cattle raising activity.